IMPLEMENTATION OF QUR'AN MEMORIZATION ACTIVITIES AT MAN 2 PALEMBANG - Muhamad Yahya; Febriyanti Febriyanti; Lalu Surya Jagat; Indah Rahayu; Ahmad Hariyadi (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This study aimed to determine the implementation of memorizing the Al-Qur'an at MAN 2 Palembang. The type of qualitative writing approach used in this study uses a qualitative descriptive approach, meaning that the data collected is not in the form of numbers but instead in the form of interview scripts, field notes, and pictures. The authors use data collection methods like observation, interviews, and documentation to obtain accurate data. The writing analysis used by the writer is data reduction, data presentation, and conclusion drawing. Based on the results of the research conducted, it is known that the implementation of Al-Qur'an memorization activities at MAN 2 Palembang is quite good, which is reflected in indicators 1) the implementation process is adjusted to the abilities of students; 2) good in terms of material; 3) method, so that it does not become a psychological burden for students during the process of memorizing activities carried out to completion. Supporting factors for memorizing the Qur'an at MAN 2 Palembang, namely 1) Physical and good psychological students; 2) awards or certificates given to students when they complete their memorization; 3) facilities, such as MP3 murotal, memorization cards, and others; and 4) maximum attention from the teacher and the facilities provided by the school are adequate. While the inhibiting factors are 1) students' laziness; 2) students are given little time to deposit memorization by the school; 3) lack of attention from parents to supervise student memorization; 4) the influence of the less supportive environment.